INTERAKSI MANUASIA DAN KOMPUTER : MENGUATKAN FUNDAMENTAL DAN PELATIHAN MICROSFT WORD UNTUK SISWA/I MADRASAH TSANAWIYAH MATHLA'UL ANWAR) - Khoirunnisya; Agus Budi Prasetyo; Tio Adrian (Abdi Jurnal Publikasi, 2025)
This research and training aims to improve basic understanding and skills in using Microsoft Word for students of Madrasah Tsanawiyah Mathla'ul Anwar with the Human Computer Interaction (HCI) approach. Based on initial findings, most students have a low level of digital literacy and minimal experience in using computers. Therefore, the training was designed with a gradual and practical approach that prioritizes a simple interface, direct feedback, and a non-intimidating learning atmosphere. The implementation method was carried out through five sessions, starting from an introduction to computers and the Microsoft Word interface, to independent practice in compiling documents. Evaluation was carried out through observation, assessment of practical results, and interviews with students and accompanying teachers. The results of the training showed that 80% of students were able to compile simple documents independently, understand the basic functions of the application, and show increased motivation and self-confidence. The conclusion of this activity is that the application of the HCI principle significantly increases the effectiveness of Microsoft Word learning for madrasah students. HCI not only helps from the technical side, but also from the affective and psychological side of students, creating a positive, adaptive, and empowering learning experience. This training is an important first step in bridging the digital skills gap in religious education environments.